Knowledge transfer between expatriates and host country nationals: contribution of individual and social capital factors - Ismail, Maimunah; Sobri, Sayang Syamira; Zulkifly, Nurul Afiqah; Hamzah, Siti Raba'ah; Yamato, Eriko (Faculty of Economics, Vilnius University, 2016)
This paper presents a study on the contribution of individual factors (cultural intelligence and feedback-seeking behaviour) and social capital factors (shared vision and trust) on knowledge transfer between expatriates and host country nationals (HCNs) as perceived by expatriates. The study adopted Social Capital Theory, and Anxiety and Uncertainty Management Theory to support the theoretical framework of the investigation. Data were analysed from a sample of 90 expatriates from selected universities and multinational corporations (MNCs) in the area of Klang Valley, Malaysia. The results reveal that there is a positive relationship between individual factors as well as social capital factors and knowledge transfer. In addition, only shared vision shows a significant influence on knowledge transfer. The regression results disclose that the variables explain 24.1% of variance in knowledge transfer.